Factors influencing the intention to donate (infaq and sadaqah) among UiTMCM staff - Othman, Azhana; Ab Hasan, Zunaidah; Ibrahim, Khalilah; Ibrahim, Siti Nurul Huda; Mohamed, Noor Azzura (2023)
This study seeks to empirically explore the donors’ intention to donate (infaq and sadaqah), focusing on how the internal and external factors can support ideas about donors' propensity to make financial contributions. This study examined whether internal factors, which are attitude and belief and also external factors, trust in charities and charity project, influence people’s general attitude towards donation and their intention to donate. A non-experimental study survey technique was implemented. Descriptive and inferential analyses were carried out using a multiple linear regression model (MLR). The results show that attitudes, trust, belief and charity project predict the intention to donate. This study is subject to size limitation.The finding may not encompass the most recent development in the field of charity project in Malaysia. Further research is needed to explore the variety background of donors and to identify additional factors influencing the intention to donate to make financial contribution. Gaining a better understanding of donors and their motivations can help organizations to make informed decisions. This study contribute to the existing literature by highlighting the significance of charity project in Malaysia and addressing the internal and external factors influencing donors to make financial contribution.